The Effect of Mind Mapping Strategy on Students’ Writing in Recount Text of X Grade at SMA Swasta Kampus Nommensen Pematangsiantar - Indah Peronika Siahaan; Selviana Napitupulu (Educate : Journal of Education and Learning, 2026)
Writing is an essential skill in English learning, especially in writing recount texts, which require students to organize ideas chronologically and coherently. However, many students still face difficulties in generating ideas, organizing content, and maintaining motivation in writing. This study aimed to analyze the effectiveness of the Mind Mapping Strategy on students’ writing ability in recount text of X grade at SMA Swasta Kampus Nommensen Pematangsiantar. This research employed a descriptive qualitative research design. The participants of this study were 23 students selected through purposive sampling. The data were collected through writing tests (pre-test and post-test), observations, and open-ended questionnaires. Students’ writing was assessed using an analytic scoring rubric covering content, organization, vocabulary, language use, and mechanics. The findings showed a significant improvement in students’ writing ability after the implementation of the Mind Mapping Strategy. The mean score increased from 69.09 in the pre-test to 87.45 in the post-test. The results indicate that mind mapping helped students generate ideas, organize their thoughts, and write more coherent recount texts. Therefore, it can be concluded that the Mind Mapping Strategy is effective in improving students’ writing skill in recount text and is recommended for use in teaching writing at the senior high school level.